Work‐related stress in a humanitarian context: a qualitative investigation. Issue 4 (13th March 2018) - Jachens, Liza; Houdmont, Jonathan; Thomas, Roslyn
Abstract : There is a paucity of research on the subjective stress‐related experiences of humanitarian aid workers. Most evaluations of stress among these individuals focus on trauma and related conditions or adopt a quantitative approach. This interview‐based study explored how 58 humanitarian aid workers employed by a United Nations‐aligned organisation perceived the transactional stress process. The thematic analysis revealed eight main topics of interest: an emergency culture was found where most employees felt compelled to offer an immediate response to humanitarian needs; employees identified strongly with humanitarian goals and reported a high level of engagement; the rewards of humanitarian work were perceived as motivating and meaningful; constant change and urgent demands resulted in work overload; and managing work–life boundaries and receiving positive support from colleagues and managers helped to buffer perceived stress, work overload, and negative health outcomes. The practical implications of the results are discussed and suggestions made in the light of current research and stress theory.